Mathematics remedial intervention for indigenous pupils with learning difficulties: does it work? - Poon , Cheng Yong; Yeo , Kee Jiar; Noor Azlan Ahmad Zanzali, (Universiti Kebangsaan Malaysia, 2012)
A systematic and explicit instruction using the concrete-representation-abstract sequence is commonly used for diagnostic and remedial approaches. However, this instructional approach might prevent pupils with learning difficulties to think and reason during mathematics learning. In this study, the authors integrated behaviorist and constructivist approach to help indigenous pupils learn addition and subtraction of whole number using manipulative and drawings. The usual practice in mathematics remediation and effect of an alternative instructional approach were investigated. Using a case study design, a teacher and six indigenous pupils were involved. Data was collected using observation, pupils' work, and interview. Analysis process involved transcribing, segmenting, coding, creating themes, and inter-relating themes. Results indicated that explicit instruction and drill-and-practice were commonly used in the mathematics remediation classroom. Pupils were weak in conceptual understanding and also arithmetic skills. However, participation in mathematical processes and extensive use of physical, pictorial, and symbolic representations of mathematical ideas had helped the participating pupils gained firm conceptual understanding of addition and subtraction, and thus improved their arithmetic skills. Some pupils responded positively towards constructivist approach of instruction but others still needed explicit and individual instruction from their teacher.